Physiological cardiac reserve: development of a non-invasive method and first estimates in man. Issue 3 (1st March 1998) - Cooke, G A; Marshall, P; Al-Timman, J K; Wright, D J; Riley, R; Hainsworth, R; Tan, L B
Abstract : Objective: To investigate whether physiological cardiac reserve can be measured in man without invasive procedures and whether it is a major determinant of exercise capacity. Design: Development of method of measurement and an observational study. Setting: A regional cardiothoracic centre. Subjects: 70 subjects with a wide range of cardiac function, from heart failure patients to athletes. Methods: Subjects underwent treadmill, symptom limited cardiopulmonary exercise tests to measure aerobic exercise capacity (represented by V˙o 2 max) and cardiac reserve. Cardiac output was measured non-invasively using the CO 2 rebreathing technique. Results: Cardiac power output (CPOmax ) at peak exercise was found to be significantly related to aerobic capacity: CPOmax (W) = 0.35 + 1.5V˙o 2 max (l/min), r  = 0.87, p < 0.001. It also correlated well with exercise duration ( r  = 0.62, p < 0.001), suggesting that cardiac reserve is a major determinant of exercise capacity. In the study, cardiac reserve ranged from 0.27 to 5.65 W, indicating a 20-fold difference between the most impaired cardiac function and that of the fittest subject. Conclusions: A non-invasive method of estimating physiological cardiac reserve was developed. The reserve was found to be a major determinant of exercise capacity in a population of normal subjects and patients with heart disease. This method may thus be used to provide a clearer definition of the extent of cardiac impairment in patients with heart failure.